How veganism impacts tourists attitudes toward tourism destinations: An empirical study - Cavalinhos, S.; Bilro, R. G.; Miguel, L. (Proceedings of the 51st Annual EMAC Conference (EMAC 2022), 2022)
The purpose of this study is to examine the structural relationships of the veganism motivations on the vegan tourist attitudes towards the tourist destination offers, and consequently on satisfaction, intention to revisit and recommend. Food and tourism are intimately related in many ways, and a growing trend towards vegan food consumption and lifestyle could pose a challenge for the tourism sector. This paper presents the conceptual framework and research design of the study. Multivariate analysis techniques, such as reliability analysis, factor analysis, and structural equation modelling will be used to validate the proposed measurement and structural model. This study intends to contribute with new insights on the vegan tourist and how vegan tourist destinations can improve this type of tourist experience in this growing segment.